Pelaksanaan Pembatalan Partai Politik sebagai Peserta Pemilihan Umum oleh Komisi Pemilihan Umum dalam Pemilihan Umum Legislatif di Kota Solok Nomor 18 Tahun 2023 tentang Pengelolaan Dana Kampanye - Shiva Alia Maharani; Aermadepa Aermadepa; Yulfa Mulyeni (AHKAM, 2026)
Campaign fund management is an important aspect of maintaining the transparency, accountability, and integrity of General Elections. Although previous studies have extensively discussed campaign funds from the perspectives of supervision and accountability, studies on the cancellation of political parties as election participants due to failure to submit the Initial Campaign Fund Report (LADK) remain limited. This study aims to analyze the implementation of the cancellation of political parties as participants in the Legislative General Election by the Solok City General Elections Commission (KPU) based on General Elections Commission Regulation Number 18 of 2023 concerning Campaign Fund Management and to explain the resulting legal consequences. This study used an empirical sociological legal method with a descriptive qualitative approach. Data were collected through semi-structured interviews with the Solok City KPU and document studies of regulations and official decisions. The results show that the Solok City KPU canceled the participation of the Indonesian Solidarity Party, Garuda Party, and Ummat Party through Solok City KPU Decision Number 9 of 2024 because they did not submit the LADK. This cancellation resulted in legal consequences in the form of the loss of status as election participants, the disqualification of legislative candidates, and a reduction in the public’s political choices. This finding emphasizes the importance of political parties’ compliance with campaign fund reporting obligations as an instrument for maintaining electoral accountability and integrity. The implications of this study provide a basis for election organizers and political parties to strengthen administrative compliance, campaign fund transparency, and the governance of election participants in accordance with statutory regulations.